UTILIZATION OF MARINE FUNGAL Nodulisporium sp. KT29 METABOLITES TO IMPROVE THE PRODUCTION PERFORMANCE OF MARINE CULTURE OF WHITE SHRIMP - Fazril Saputra; Dinamella Wahjuningrum; Kustiariyah Tarman; Irzal Effendi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
This study aimed to determine the best dose of administration of marine fungal Nodulisporium sp. KT29 metabolites to improve the production performance of marine culture of white shrimp. The experimental animals used were white shrimp Litopenaeus vannamei post larvae 12, which were reared in the sea using floating net cages with a stocking density of 700 post larvae/net. Experimental design used was a completely randomized design consisting of 3 treatments with 3 replications; control without the administration of Nodulisporium sp. KT29 metabolites, dietary of feed containing Nodulisporium sp. KT29 metabolites at doses of 20 mL/kg of feed and 40 mL/kg of feed. The results showed that survival rate, absolute length growth, weight gain, daily growth rate and feed conversion ratio in treatment groups were better than the control (P<0.05). The administration of marine fungal Nodulisporium sp. KT29 metabolites at a dose of 20 mL/kg of feed could improve the production performance of white shrimp cultivated in the sea with survival rate, daily growth rate and feed conversion ratio: 66.61±6.94%, 20.18±0.39 %/day and 3.20±0.22, respectively.